텍스트마이닝 기법을 이용한 국내 산림 작업 및 작업 안전 연구 동향 분석 - 최예준; Ye Jun Choe; 이준우; Joon-woo Lee; 최성민; Sung-min Choi (한국산림과학회지, 2025)
최근, 산림 작업은 그 범위가 점차 확대되며, 지속 가능한 산림경영의 실현을 위한 필수 요소로 부각되고 있다. 또한, 중대재해처벌법의 시행 등으로 인해 산림 작업 안전의 중요성이 강조되고 있음에도 불구하고, 타 산업에 비해 높은 재해율을 보이며, 관련 연구가 미흡한 실정이다. 이에 따라, 산림 작업의 효율성과 안전성을 제고하기 위해 선행 연구의 동향을 파악하고 후속 연구의 방향을 제시하는 연구가 필요한 시점이다. 따라서, 본 연구는 텍스트마이닝(Text-Mining) 기법을 이용하여 국내 산림 작업 및 산림 작업 안전과 관련된 연구 동향을 분석하고 주요 연구 주제를 도출하기 위해, TF-IDF 분석, LDA 토픽분석, 동시출현빈도 기반 단어망 분석(N-gram, 클러스터링 분석)을 수행하였고, 시기별 분석을 통해 시대 흐름에 따른 연구관심도 변화를 살펴보았다. 연구 결과, 산림 작업 분야는 산림 자원의 효율적 활용, 작업 기계화 및 시스템 개선, 작업 시간·비용 절감에 중점을 두고 있었으며, 작업 안전 분야는 물리적 부담과 안전 확보, 노동자 처우 개선, 심리·사회적 요인에 대한 대응, 제도적 기반 마련이 주요 연구 흐름으로 나타났다. 시계열 분석에서는 시대별로 부각된 키워드를 통해 연구 흐름이 기술 중심에서 제도와 사람 중심으로 전환되고 있음을 확인하였으며, 이를 바탕으로 기계화와 생산성, 안전 기술, 교육 효과, 정책 변화에 따른 연구 등 다양한 후속 연구 방향을 제시하였다. 종합적으로 본 연구는 산림 작업의 효율성과 안전성을 확보하기 위한 학술적 기반을 마련하고, 향후 연구 방향을 제시하여 산림 산업 및 정책 수립에 기여할 수 있을 것으로 기대된다. The scope of forest operations has recently gradually expanded, and forest operations are deemed an essential component for the achievement of sustainable forest management. Emphasis on forest work safety is increasing, particularly after the enforcement of the Serious Accidents Punishment Act. However, the forestry sector continues to exhibit higher accident rates than other industries, and related research remains insufficient. Therefore, trends evident in previous studies must be identified, and directions must be provided for future research initiatives aimed at improving the efficiency and safety of forest operations. This study applied text-mining techniques to analyze research trends related to forest operations and forest work safety in Korea and derive the major research topics. Specifically, it employed TF-IDF analysis, LDA topic modeling, and co-occurrence-based network analysis (including N-gram and clustering). It also conducted a time-series analysis to examine shifts in research interests over time. The study results revealed that extant investigations on forest operations have focused primarily on the efficient use of forest resources, mechanization and system improvement, and time and cost reduction. Conversely, studies on forest work safety have emphasized physical burden and accident prevention, probed the improvement of worker conditions, queried psychosocial factors, and scrutinized institutional support systems. The time-series analysis disclosed shifts in research focus from technical aspects to institutional and human-centered themes, as evidenced by the emergence of keywords such as “excavator,” “stress,” and “safety” in discrete decades. The study findings enable the delivery of several directions for future investigations. For instance, prospective researchers could attempt quantitative analyses of mechanization and productivity, examine the application of smart safety technologies, conduct empirical studies on training effectiveness, and evaluate research trends associated with policy changes. In conclusion, this study provides a scholarly foundation for the enhancement of the efficiency and safety of forest operations. Thus, it expects to contribute substantively to future academic research and policy-making endeavors in the forest sector.